MENATAP MASA DEPAN INDONESIA DALAM DUNIA EKOLOGI MODERN: Pembacaan Fenomenologis Relasi Manusia dengan Ekologi Ditinjau dari Pemikiran Martin Heidegger - Usman, Yosef; Riyanto, Fransiskus Xaverius Eko Armada; Adon, Mathias Jebaru (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The existence of ecology in Indonesia is one of the discourses that should be studied and language in the public or private sphere. The essence and existence of ecology in Indonesia is a crucial and important ultimate value in the discourse of metaphysical philosophy. The focus of this research discourse is to confront Heidegger's thoughts related to human existential relations (dasein) which cannot be separated from the surrounding natural environment. Uncovering one aspect of the value of harmonization and order, namely relations with fellow humans, and nature and other creations on this Indonesian earth. By looking at ecological realities like this, humans (Dasein) must see the overall influence and impact that will occur in the next twenty-five years. 1) Humans (Dasein) wake up from their deep sleep over the shackles of